HYDRAULIC CONDUCTIVITY ESTIMATES FOR QUATERNARY AND UPPER CRETACEOUS WATER-BEARING COLLECTORS VS VELOCITY OF CARBONATE ROCK DISSOLUTION AT RIVNE NPP - Brovko, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The goal of the research is to estimate a hydraulic conductivity effect on karst processes and to identify correlations between the hydraulic conductivity values and Ca2+ content in groundwater based on systematic and statistical techniques, GIS methods, and comparative analysis. There has been established a correlation between the values of free calcium ions in groundwater of the Quaternary and Upper Cretaceous aquifers and their hydraulic conductivity, with it being direct one in vivo and inverse one in artificial conditions for the Quaternary aquifers, with inverse one in vivo and direct one in artificial conditions for the Upper Cretaceous aquifers. GIS method was employed to determine hydraulic conductivity at modern monitoring network observation posts as of the past. Non-parametric correlation method and Spearman rank coefficient were used to identify the correlation between hydraulic conductivity and the values of free calcium ions in groundwater. There was carried out a comparative analysis of the data obtained in the natural and artificial conditions. Direct and inverse correlations being established for the Quaternary and Upper Cretaceous aquifers, it enhances exploitation of water bearing collectors, and facilitates understanding how artificial conditions affect hydrochemistry of the environment and engineering geology.
Keywords: groundwater; hydraulic conductivity; Rivne NPP